Sex-specific expression of apolipoprotein levels following replenishment of vitamin D. Issue 180 (June 2018) - Al-Daghri, Nasser M.; Wani, Kaiser; Sabico, Shaun; Garbis, Spiro D.; Chrousos, George P.; Amer, Osama E.; Ansari, Mohammed Ghouse Ahmed; Al-Saleh, Yousef; Aljohani, Naji J.; Al-Attas, Omar S.; Alokail, Majed S.
Highlights: The effect of vitamin D supplementation in apolipoproteins is limited. Vitamin modifies apolipoproteins, particularly the apolipoproteins B and C class. Effects of vitamin D on apolipoproteins are sexually dimorphic. Abstract: Numerous studies have been done to establish the relationship between vitamin D and lipids, yet a definitive causal link is not found. This interventional study aims to evaluate and compare levels of apolipoproteins among vitamin D deficient subjects at baseline and after they achieved full vitamin D status correction.120 Saudi adults with vitamin D deficiency [25(OH)D < 50nmol/l] were recruited and given 50, 000IU cholecalciferol weekly for first 2 months, then twice a month for next 2 months, followed by daily 1000IU until month 6. Blood samples were taken at baseline and after 6 months. Serum 25(OH)D, lipid profile and apolipoproteins (A1, A2, B, C1, C2, C3, E and H) were analyzed using commercially available kits. Overall, serum 25(OH)D increased significantly(63.3 ± 16.5nmol/l at end of study vs. 32.5 ± 10.8 at baseline; p < 0.0001). In parallel, a significant increase in apolipoproteins C1, C2, C3 and E (all p-values < 0.01) and a significant decrease in apolipoprotein B (p = 0.02) was observed. Following, stratification according to sex, apolipoproteins C2 and C3 significantly increased only in males (p-values < 0.01) while apolipoprotein C1 significantly increased only in females (p < 0.01). In addition, apolipoprotein B significantly decreased only in females (p = 0.002). These results suggests role of vitamin D in modulation of circulating levels of lipoproteins. The sexual dimorphism observed in circulating levels of measured apolipoproteins following vitamin D correction may explain, in part, known sexual disparity in the events of cardiometabolic health.